2001
DOI: 10.1042/bj3600097
|View full text |Cite
|
Sign up to set email alerts
|

Mutations to Gly2370, Gly2373 or Gly2375 in malignant hyperthermia domain 2 decrease caffeine and cresol sensitivity of the rabbit skeletal-muscle Ca2+-release channel (ryanodine receptor isoform 1)

Abstract: and K3940A were made in two potential ATPbinding motifs (amino acids 2370-2375 and 3937-3940) In the presence of 1 mM AMP-PCP, Ca# + -activation curves were shifted to higher affinity and maximal binding was increased to a similar extent for wild-type RyR1 and mutants. ATP sensitivity of channel opening was also similar for wild-type INTRODUCTIONCa# + -release channels of sarcoplasmic reticulum (ryanodine receptors, or RyRs) are large homotetrameric molecules with molecular masses of $ 2.26 MDa [1][2][3][4].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In addition, RyR1 I404M expressed in dyspedic mice myotubes exhibited resting [Ca 2+ ] levels and SR Ca 2+ content comparable to that of the wild type [85]. Furthermore, expressions of RyR1 D3987A and G3939A rabbit cDNA in HEK-293 cells, which correspond to the positions of MH-associated mutations D3986E and G3938D in humans, respectively, showed responses to activation by [Ca 2+ ], caffeine, and 4-CmC comparable to that of wild type [92,95]. For these mutations where no clear functional effect has been observed, it is of course possible that they are not causative of the disease but, instead, simply represent polymorphisms.…”
Section: Highlight Of the Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, RyR1 I404M expressed in dyspedic mice myotubes exhibited resting [Ca 2+ ] levels and SR Ca 2+ content comparable to that of the wild type [85]. Furthermore, expressions of RyR1 D3987A and G3939A rabbit cDNA in HEK-293 cells, which correspond to the positions of MH-associated mutations D3986E and G3938D in humans, respectively, showed responses to activation by [Ca 2+ ], caffeine, and 4-CmC comparable to that of wild type [92,95]. For these mutations where no clear functional effect has been observed, it is of course possible that they are not causative of the disease but, instead, simply represent polymorphisms.…”
Section: Highlight Of the Resultsmentioning
confidence: 79%
“…Commonly used is a [ 3 H]ryanodine binding assay ( Figure 4C) [19,51,54,60,67,77,79,86,90,92,93,95,96,103,105,108,113,129] As opposed to whole-cell measurements, activities of a single channel can be recorded using planar lipid bilayer electrophysiology ( Figure 4D) [19, 53, 54, 67, 69, 77, 79, 99-101, 105, 107, 108, 111, 112, 114]. Recombinant or endogenous RyR from crude SR vesicle preparations or from purified material are fused into an artificial lipid bilayer formed across two chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Other possible ATP binding sites suggested for RyR1 are similar to those present in chaperon proteins such as GroES [35].…”
Section: Lipid Planar Bilayersmentioning
confidence: 94%
“…Studies utilizing mutations, deletions, or chimeras of the RyR1 have suggested the existence of regions that regulate the caffeine binding sites [35,48]. Substitution of all 3 Gly, in the motif from amino acids 2370 to 2375, by Ala showed that this motif played a role in the sensitivity of the RyR1 for caffeine.…”
Section: Ryanodine Receptor Type 1 and Purinesmentioning
confidence: 98%
See 1 more Smart Citation